Delineation of groundwater potential zones in Singrauli coalfield using remote sensing, GIS and multi-influencing factor (MIF) techniques, India - Sonkar A.K.; Varshney R.; Vishwakarma A.K.; Jamal A.; Barman S.K. (My University, 2025)
The present research was carried out for delineation of groundwater potential zones in the Singrauli coalfield utilizing combined application of remote sensing, GIS and multi-influencing factor techniques (MIF). The groundwater potential zones (GWPZ) were delineated using six thematic layers like lineament density, land use–land cover (LULC), geology, drainage, slope, and soil. Various tools of ArcGIS were used to digitize and convert these thematic maps into raster data. In addition to it, MIF technique was used to assign fixed score and weight to the components of these raster maps. Furthermore, each weighted thematic layer was statistically calculated to get the GWPZ. The obtained resulting GWPZ were classified into four classes, namely very good, good, very poor, and poor. The groundwater potential zone map indicated very good to good groundwater potential in the plains including cropland, while gentle to moderate slope was found in Talchir and Barakar formation as well as in the pediplains. The LULC, slope and geology have played a major role in the formation of very good groundwater potential zone. Poor to very poor groundwater potential was found in and around the mining area, forest/hilly area with a steep slope, metamorphic terrain and built-up area. These findings may further help the local authorities for enhancing groundwater resource planning in the study area. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.